A gender-sensitive intervention in jail: A study of Italian men convicted of assaulting women or femicide. (November 2020) - Testoni, Ines; Pedot, Mara; Arbien, Maibrit; Keisari, Shoshi; Cataldo, Evelina; Ubaldi, Consuelo; Ronconi, Lucia; Zamperini, Adriano
Highlights: Femicide is a huge problem all over the world caused by hegemonic maschilism. Arts therapies are considered to be effective methods for raising awareness. Psychodrama and PhotoTherapy increase socio-emotional skills and can be used in prison. This art-therapy intervention in prison was effective in changing offenders' sexism. Abstract: Gender-based violence is deeply rooted in hegemonic masculinity and patriarchy, the source of both hostile and benevolent sexism. This study is an assessment of a gender-sensitive intervention realized through photo-based therapy and psychodrama, conducted in 9 sessions with 9 male prisoners detained in north-eastern Italy who are convicted of assaulting or murdering women. The research adopted a qualitative method design in analysing the interview texts, carried out with the Client Change Interview and the Helpful Aspects of Therapy, and the transcribed reports from all 9 sessions. The findings revealed that the intervention transformed the participants' hostility into benevolent sexism and that they had replaced their concepts of machismo and honor with a new representation of the ideal man as a "maternal father." This shift was a result of a consciousness-raising process that recognizes the value of emotions and the need for empathic relationships.